English L2 reading : getting to the bottom - Birch, Barbara M.; Fulop, Sean A. (New York, NY ; London : Routledge, 2021)
English L2 Reading: Getting to the Bottom uses research-based insights to examine bottom-up skills in reading English as a second language. This fourth edition clearly presents core concepts alongside their practical applications to teaching contexts, with updated research findings, a new focus on metalinguistic awareness, and new resources for students. The text's pedagogical features help readers connect linguistic details and psycholinguistic theory with practical explanations and teaching suggestions. Pre-reading Questions challenge readers to analyze their own experiences. Study Guide Questions allow readers to review, discuss, and assess their knowledge. Discussion Questions elaborate on themes in each chapter, while the new Language Awareness Activities help develop metalinguistic awareness. Three Appendices provide tables that list the graphemes and the phonemes of English, as well as a brand-new dictionary pronunciation guide. New to the fourth edition: Substantially revised and updated research on linguistics New, evidence-based models on the reading process Language Awareness Activities that highlight metalinguistic awareness Word study examples in each chapter For teachers, teacher trainers, reading researchers, or anyone interested in teaching reading, this popular, comprehensive, myth-debunking text provides clear and practical guidance towards effectively supplementing top-down teaching approaches with bottom-up reading strategies.
Cover -- Half Title -- Series -- Title -- Copyright -- Dedication -- Contents -- Preface -- Acknowledgments -- 1 The Beginning Reader -- 2 Writing Systems -- 3 Interlanguage Reading and Transfer -- 4 Listening Skills in Reading -- 5 Processing Letters -- 6 The English Spelling System -- 7 Approaches to Phonics -- 8 English Morphophonemic Spelling -- 9 Spelling Development -- 10 Vocabulary Acquisition -- 11 Getting to the Bottom of English L2 Fluency -- Appendix A English Graphemes -- Appendix B English Phonemes and Their Principal Spellings -- Appendix C Dictionary Transcription -- Index
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Study and teaching -- Foreign speakers; Second language acquisition; Reading comprehension; EDUCATION / General; EDUCATION / Bilingual Education